Adicción al uso de dispositivos tecnológicos y su influencia en el comportamiento de un niño de 6 años - Chang Peñaherrera, Karina Stefania (2020)
At present, the concept of addiction is not exclusively related to the consumption of chemical substances or drugs, such as: opiates, alcohol, tobacco, cocaine, amphetamines, benzodiazepines, etc. The concept of addiction can also be associated with apparently healthy and non-dangerous behaviors or behaviors. These behaviors, can become addictive, depending on the force, the assiduity or the amount of time and money that it invests in carrying them out to seriously interfere with the operation of the subject. We refer for example to: the use of the internet, sex, work, shopping, food, games, etc. The subject of the present case study addresses the addiction to the use of technological devices and their influence on the behavior of a 6-year-old child, for this reason a series of research procedures immersed within the clinical-psychological method were performed, in its phases we have, the justification, presentation of the objective, the theoretical support in which the work is affirmed, the methodology, diagnostic evaluation techniques, the results obtained from its application, the detected situations, proposed solutions, the conclusions and bibliography. Having as a diagnosis addiction to technological devices, highlighting that American association of psychiatry and the world health organization has only approved within the category of behavioral addictions, the pathological game, associated with this we have problems in the parent-child relationship, as a consequence of the separation of these for what is implemented a psychological intervention of cognitive-behavioral cut that yielded satisfactory results.